External Validation of the DHAKA Score for Diagnosing Severe Dehydration in Children with Acute Diarrhea in Resource‐limited Settings. (19th April 2017) - Levine, Adam C.; Glavis‐Bloom, Justin; Modi, Payal; Nasrin, Sabiha; Atika, Bita; Rege, Soham; Schmid, Christopher H.; Alam, Nur H.
Abstract : Background: Acute diarrhea remains both common and deadly in children worldwide. Proper treatment depends on accurately assessing dehydration status. Current World Health Organization (WHO) guidelines include an algorithm for classifying children as having no, some, or severe dehydration, which has never been properly validated. The Dehydration: Assessing Kids Accurately (DHAKA) study recently derived a new scoring system for dehydration in children, but it requires external validation. Methods: Our study enrolled a random sample of children with acute diarrhea in Bangladesh. Local nurses prospectively applied both the DHAKA score and the WHO algorithm to children on arrival and obtained serial weights as they were rehydrated. The percent weight change with rehydration was used to classify subjects with severe (>9%) dehydration, some (3%–9%) dehydration, or no (<3%) dehydration. Test characteristics and the area under receiver operator characteristic curves (AUC) were calculated and compared for both diagnostic tools. Results: A total of 546 children were enrolled, with 488 included in the final analysis. The DHAKA score had an AUC of 0.77 compared to 0.72 for the WHO algorithm for the diagnosis of severe dehydration (p = 0.001) and 0.84 compared to 0.62 for the diagnosis of any dehydration (p < 0.001). The DHAKA score had a sensitivity of 86% and specificity of 54% for diagnosing severe dehydration and 93 and 50% for diagnosing any dehydration. Conclusion: The DHAKA score is now the first dehydration assessment tool both derived and validated in resource‐limited settings, and it outperformed the WHO algorithm. Frontline providers may use this new tool to better manage acute diarrhea in children. Figure 1 DHAKA score.